PENINGKATAN PENGETAHUAN DAN DEMONSTRASI PENANGAN DISMINORHEA PADA REMAJA SMP - W. Winarni (P3M Universitas Aisyiyah Surakarta, 2017)
Disminnorhea is one of the menstrual disorders that often occur in adolescens. 50% of sufferers often experience lack of disminorerhea the inability of daily activities. Therefore needs to be done as preventive treatment with mild as well as sports consume fruits and vegetables. Almost teens don’t know don’t know about how to handle disminorhea, so need to do some socializing and the demo aboutnstration to handle disminorhea correctly. The target participants are expected external socializtion can understand the importance of the knowledge of the menstrual Disorders especially disminnorhea as well as have the abbility to perform actions handling Disminorhea independently.The activities of socialization in SMPIT Nur Hidayah Surakarta, with using extension lectures method and demonstrations. The results of participant extension can understand and pursuing the action handler disminorhea correctly, so need to be held educations about health is not only limited to the handling of disminorhea but also in adolescent reproduktive health improvement